Implementation of Marketing Mix in Nature Tourism Services Management A Qualitative Study on Muji Trekker - Hizmi, Surayyal; Pidada, Ida Ayu Yadnya Sari Dewi Utami; Mahawira, Komang; Nawawi; Chandra, Ahsan (Politeknik Pariwisata Bali, 2025)
This study aims to explore the implementation of the marketing mix strategy (4Ps) by Muji Trekker, a community-based hiking tour service provider in Sembalun area, West Nusa Tenggara. This study uses a qualitative approach with data collection techniques in the form of in-depth interviews and field observations. The findings show that Muji Trekker implements a product strategy through the provision of various climbing packages (Deluxe, Standard, and Budget) based on market research and consumer economic conditions. The pricing strategy is applied with a segmentation approach, where rates for foreign tourists are adjusted to higher operational costs. In promotion, Muji Trekker emphasises organic and relational methods such as social media, word of mouth, and customer testimonials over paid advertising. Meanwhile, the people aspect is a key element in the success of the service; guides not only act as technical facilitators, but also as friends and representations of local values that create an immersive experience for tourists. This study also shows that the 4P strategy is adaptive and contextualised, with limited resources encouraging innovation and creativity. Strategically, this relationship-based approach can be used as an alternative model for community tourism development in non-urban areas. The academic implications of this research enrich the tourism service marketing literature with empirical evidence from unexplored local areas, and encourage digital training policies and human resource capacity building in the experiential tourism sector.